Collective savings pension policy in an economy with heterogeneity and informality; Sistema de pensiones de ahorro colectivo en una economía con heterogeneidad e informalidad - Elías Albagli; Agustín H. Arias Gutiérrez; Markus Kirchner (Estudios de Economía, 2024)
We compare the macroeconomic effects of a fully funded individual defined contribution (IDC) pension scheme, an unfunded pay-as-you-go (PAYG) system, and a collective defined contribution (CDC) regime. Under the latter, contributions of workers from a given cohort are invested in capital markets and repaid to that cohort upon retirement; its collective nature arises from an intragenerational progressive redistributive rule. Our results from an overlapping generations model calibrated for Chile show that the CDC scheme has similar macroeconomic effects as an IDC plan, including a moderate positive effect on the formal labor market, aggregate savings, and output. The PAYG system has negative effects on all these dimensions. Critical for the success of the CDC scheme is conditioning benefits on contributions, to incentivize formal labor status. We conclude that a CDC policy stands as a sustainable alternative for countries with significant labor informality and income inequality.
Keywords: E26; E27; H55; J46; 330; Overlapping generations models; Pension system; Informal labor market; Heterogeneous agents